Peran Komunikasi Politik Simbolik dalam Membentuk Perilaku Ekonomi Digital Pemuda di Era Media Sosial: Studi Kasus pada Pemuda di Karanganyar - Athifah Leony Khoridah; Dzikrina Aqsha Mahardika; Lisna Nurul Widyaningrum; Yelinda Nur Auliana Arimbi; Fitiani; Azis Rafi Baskara; Agus Susilo; Ihsyan Kolefiyan (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The rapid growth of digital technology and social media has reshaped how young people engage in economic activities, positioning symbolic communication as a key behavioral driver in the digital economy. This study examines the influence of symbolic political communication on the digital economic behavior of youth in Karanganyar, focusing on how symbols, messages, and visuals affect decision-making. Using a quantitative causal design with 75 respondents aged 18–25, data were gathered through online questionnaires. Validity and reliability tests confirmed strong consistency (Cronbach’s Alpha = 0.788; correlations > 0.361). Results reveal that visual appeal, message reliability, and symbolic credibility on social media significantly impact promotional behavior, consumer trust, and personal branding. Most respondents predominantly female and digitally active indicated that social media symbols shape both consumption and entrepreneurial engagement. The findings highlight that symbolic communication operates not only as an expressive tool but also as an economic mechanism enhancing credibility, collaboration, and competitiveness in digital entrepreneurship. Ultimately, symbolic representation plays a vital role in shaping digital economic identity and sustaining youth participation in the evolving digital economy.